A comparative study on AC/DC analysis of an operational low voltage distribution system - Cihan Katar; Cengiz Polat Uzunoglu (Institute of Advanced Engineering and Science, 2021)
In the near future, the digitalizing world will continue to improve and the need for DC based devices will be increased beyond doubt. Today’s electrical grid is strictly dependent on AC-DC rectifiers. Each conversion process means additional power losses and signal quality deteriorations for the network. In addition, networks which are fed by batteries and renewable sources such as solar panels, and wind turbines are suffering from conversion-based power losses. In this respect, the idea of switching to DC on the low voltage side of the networks has become an intriguing subject. In this study, the applicability and efficiency of the low voltage direct current (LVDC) concept for low voltage distribution systems is discussed and a sample LVDC distribution system is analyzed. In this operational residential application electrical transient analyzer program (ETAP) is employed for comparison of different voltage levels such as 110 VDC, 250 VDC, 320 VDC and conventional 220/380 VAC. As a novel approach different DC voltage levels are compared with typical AC system in detail. Comparative analysis is conducted for safety regulations, voltage drops, current carrying capacities, power consumption and harmonic calculation of the proposed system. In this respect applicability, possible drawbacks and future aspects of LVDC systems are interpreted.